Evaluation of Antibacterial Potential of Carbonated Hydroxyapatite Combined with Propolis on Porphyromonas gingivalis - Nungky Devitaningtyas; Ahmad Syaify; Dahlia Herawati; Suryono Suryono (Majalah Obat Tradisional, 2020)
Carbonated hydroxyapatite is ideal as a bone graft material because it has similar organic matters to the bone, excellent osteoconductive properties, and good biodegradation in the body. Hydroxyapatite contains the risk of being contaminated by bacteria called Porphyromonas gingivalis (P. gingivalis) in the oral cavity because it has no vascularization, therefore, facilitating adhesion of bacteria, and when applied in the oral cavity, it may cause an infection that then inhibits healing. Thus, it is necessary to use a material that has an antibacterial effect with low potential of causing resistance to treat the postsurgical infection properly. Propolis has antibacterial, antiviral, antifungal, antitumor, and immunomodulatory activities. Propolis contains a large number of flavonoids and phenols. The phenol compound in propolis is usually called caffeic acid phenethyl ester (CAPE), and it has a good antibacterial property. The study aims to evaluate the antibacterial effect of carbonated hydroxyapatite when immersed with different propolis concentrations of 2.5%, 5%, 7.5%, and 10% for 24 h and to measure the zone of inhibition against P. gingivalis. The Kruskal–Wallis test resulted in p = 0.00 (p < 0.05), indicating that there were significant differences among the test groups. The data processing was followed by Mann–Whitney U-test, and the results showed a significant difference in the group of carbonated hydroxyapatite-10 % propolis compared with the other groups. Inhibition zone of carbonated hydroxyapatite that immersed with propolis 10% showed the largest mean of diameters zone of inhibition.